The Effect of Pre-fermentative Freezing Treatment on the Sensory Quality of ‘Meili’ Rosé Wine - Lan, Y. Y.; Tao, Y. S.; Tian, T.; Hu, Z. Y.; Peng, C. T. (South African Journal of Enology and Viticulture, 2016)
In this study, the effect of a pre-fermentative freezing treatment on quality attributes of ‘Meili’ rosé wine was assessed. Prior to fermentation, ‘Meili’ grapes (berries and must) were subjected to a freezing treatment considering factors of freezing temperatures, freezing time, and thawing method. Colour-related indices were measured by spectral methods. Wine aroma characteristics and sensory attributes were assessed by trained panellists. The results revealed that lower freezing temperature and longer freezing time had positive effects on wine quality attributes. The treatment of frozen berries might help extract colour-related compounds. Microwave thawing improved wine colour, but decreased taste quality. In the work, the MF-10°C/6 h treatment (microwave-thawed berries that had been frozen at -10°C for 6 h) contributed to the best colour characteristics, whereas the NP-20°C/4 h treatment (naturally-thawed must that had been frozen at -20°C for 4 h) contributed to the best taste attributes.